Simulation Of Sulfur Trioxide Production In An Adiabatic Multistage Catalytic Reactor - Rozman, Anis Salwani (Universiti Sains Malaysia, 2018)
The production of sulfur trioxide from sulfur dioxide gas is already gaining global importance and thus this process needs to be studied so that the conversion of sulfur dioxide is assured during its implementation in the chemical industry especially in sulfuric acid industry. It is possible to simulate sulfur trioxide production process with a well-developed simulation software such as Aspen Plus despite using the numerical simulation like previous research works. Aspen Plus Version 8.8 is used in this research study to simulate an adiabatic multistage catalytic reactor where sulfur dioxide gas is oxidized into sulfur trioxide gas in the presence of vanadium pentoxide catalyst. The simulation results obtained are compared with literature for validation. The simulated results obtained by Aspen Plus generate 4% of general average error in terms of the sulfur dioxide conversion, temperature and pressure outlet. From the sensitivity analysis conducted, it is found that the molar composition of sulfur trioxide increases lightly up to 0.082 at 2.5 bar of reactor inlet pressure while the reactor inlet temperature shows no significant effect on the molar composition of sulfur trioxide generated.